Geometric and Electronic Properties of Monolayer HfX2 (X = S, Se, or Te): A First-Principles Calculation - Huynh, Thi My Duyen; Nguyen, Duy Khanh; Nguyen, Thi Dieu Hien; Dien, Vo Khuong; Pham, Hai Duong; Lin, Ming-Fa (Frontiers in Materials, 2021)
The essential properties of monolayer HfX2 (X = S, Se, or Te) are fully explored by first-principles calculations. The optimal lattice symmetries, sublattice buckling, electronic energy spectra, and density of states are systematically investigated. Monolayer HfS2, HfSe2, and HfTe2, respectively, belong to middle-gap semiconductor, narrow-gap one and semimetal, with various energy dispersions. Moreover, the van Hove singularities (vHs) mainly arise from the band-edge states, and their special structures in the density of states strongly depend on their two or three-dimensional structures and the critical points in the energy-wave-vector space. The above-mentioned theoretical predictions are attributed to the multi-orbital hybridizations of [d_(x^2-y^2 ), dxy, dyz, dzx, d_(z^2 )] – [s, px, py, pz] in the Hf-X chemical bonds. The diversified physical phenomena clearly indicate a high potential for applications, as observed in MoS2-related emergent materials ions.